2020
DOI: 10.1002/cncy.22375
|View full text |Cite
|
Sign up to set email alerts
|

Hürthle cell lesions of the thyroid: Progress made and challenges remaining

Abstract: Hürthle cell–predominant thyroid fine needle aspirations (FNA) are encountered frequently in routine practice, yet they are often challenging to diagnose accurately and are associated with significant interobserver variability. This is largely due to the ubiquity of Hürthle cells in thyroid pathology, ranging from nonneoplastic conditions to aggressive malignancies. Although limitations in cytomorphologic diagnoses likely will remain for the foreseeable future, our knowledge of the molecular pathogenesis of Hü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 132 publications
(341 reference statements)
1
22
0
Order By: Relevance
“…Oncocytic metaplasia is a well-known nonneoplastic condition mimicking FNHCT. 2,4,25 On the other hand, approximately half of molecularly negative…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oncocytic metaplasia is a well-known nonneoplastic condition mimicking FNHCT. 2,4,25 On the other hand, approximately half of molecularly negative…”
Section: Discussionmentioning
confidence: 99%
“…1 Cellular thyroid fine-needle aspirates (FNAs) composed predominantly of oncocytic (Hürthle) cells, devoid of lymphocytes, and with scant colloid fall into an indeterminate diagnostic category and are diagnosed as follicular neoplasm, Hürthle cell (oncocytic) type (FNHCT), within the Bethesda System for Reporting Thyroid Cytopathology (BSRTC). 2,3 Distinguishing neoplastic from nonneoplastic oncocytic lesions on cytology may be challenging, whereas differentiating follicular oncocytic adenoma (FOA) from carcinoma is deferred to surgical pathology (with the risk of malignancy for thyroid nodules diagnosed as FNHCT ranging from 14% to 45%). 2 Importantly, medullary thyroid Subsets and Mimics of Oncocytic Neoplasms/Landau et al carcinoma, papillary thyroid carcinomas (PTC), intrathyroidal parathyroid nodules, oncocytic metaplasia of chronic lymphocytic thyroiditis (CLT) or nodular thyroid hyperplasia, and autonomously functioning thyroid nodules (AFTNs) may all present on preoperative cytology as FNHCT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study shows that FDG avid nodules show a relative excess of BETHESDA category IV and V FNA (see Table 4). Although the published studies included in this meta-analysis do not give specific information on the prevalence of Hurthle cell neoplasms, the finding of relatively higher frequencies of category IV and V FNA in thyroid TI implies that this is due to the underlying higher clinical ROM of PET avid thyroid nodules, in combination with a relative excess of HCN in nodules that are FDG avid which would typically fall in BETHESDA categories III and IV [14,[32][33][34].…”
Section: Discussionmentioning
confidence: 92%
“…Two studies reported recurrent RET-PTC translocations in HCCs using FISH and PCR methods ( 18 , 19 ). However, in larger cohorts using DNA-sequencing based methods, RET-PTC ( CCDC6-RET and NCOA4-RET ) translocations were not detected, nor were RET-PTC translocations recurrently identified in molecular testing of FNA specimens with Hürthle cell cytology ( 20 26 ).…”
Section: Low Frequency Of Canonical Fdtc Driver Mutationsmentioning
confidence: 96%